Analisis Yuridis Penggunaan Artificial Intelligence dalam Aktivitas Bisnis Digital di Indonesia: Tantangan Regulasi dan Kepastian Hukum - Heru Wardoyo (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
This study aims to analyze the legal regulation of the use of Artificial Intelligence (AI) in digital business activities in Indonesia, identify the regulatory challenges encountered, and formulate an ideal legal framework to ensure legal certainty in the utilization of AI technology. The research addresses two main issues: (1) how the use of AI in digital business activities is currently regulated in Indonesia, and (2) what regulatory challenges exist and what ideal legal framework can be developed to achieve legal certainty in the use of AI. This research employs a normative legal research method using a statutory approach, a conceptual approach, and a comparative approach. The legal materials consist of primary legal sources in the form of legislation and secondary legal sources, including scholarly literature, scientific journals, and relevant policy documents. The findings reveal that Indonesia has not yet enacted a specific regulation governing the use of AI in digital business activities. Existing legal provisions are dispersed across several regulations, including the Law on Electronic Information and Transactions, the Personal Data Protection Law, Government Regulation Number 71 of 2019, and the Consumer Protection Law. Consequently, these regulations have not been able to provide comprehensive legal certainty regarding AI utilization. The regulatory challenges include delays in legal development, the absence of AI risk classification, issues related to algorithmic transparency, personal data protection concerns, and unclear legal liability mechanisms. Therefore, the government is encouraged to establish a dedicated AI regulatory framework based on a risk-based approach, ensuring transparency and accountability, supported by effective oversight mechanisms to create legal certainty in digital business activities.